Population Biology and Utilization Status of Motan Fish (Thynnichthys thynnoides) in Lake Karangan, Pelalawan Regency, Riau - Aida Rama Rani; Eko Prianto; Muhammad Fauzi (SIMBIOSA, 2026)
The motan fish (Thynnichthys thynnoides) is one of the economically important fish species found in the waters of the Kampar River, including Lake Karangan, Rantau Baru Village, Pangkalan Kerinci Sub-district, Pelalawan Regency. Fishing activities that take place almost year-round, coupled with the use of fishing gear with relatively small mesh sizes, are thought to place pressure on motan fish stocks. This study aims to analyse biological parameters and determine the exploitation status of the motan fish in Lake Karangan. The research was conducted from January to March 2026 using a survey method involving sampling of fishermen’s catches. Population parameter analysis was performed using the FISAT II software, whilst the exploitation status was analysed using the Length-Based Spawning Potential Ratio (LB-SPR) method. A total of 242 motan fish were collected, ranging in length from 95–169 mm. The results of the study indicate that motan fish exhibit a negative allometric growth pattern with a b-value of 2.8205. The growth parameters obtained were asymptotic length (L∞) 175.35 mm, growth coefficient (K) 0.610 per year, and t0 of -0.31 years. The values for total mortality (Z), natural mortality (M), fishing mortality (F), and exploitation rate (E) were 2.50; 0.82; 1.69; and 0.67 per year, respectively. The results of the LB-SPR analysis indicate a first-capture length (SL50) of 105.92 mm, a first-maturity length (Lm50) of 109 mm, and a Spawning Potential Ratio (SPR) of 16%. These values indicate that the exploitation status of motan fish in Lake Karangan is in the ‘over-exploited’ category; therefore, management efforts are required through the regulation of catch sizes and the use of more selective fishing gear to support the sustainability of motan fish stocks.